Negative Effect on the Anti-Oxidant Potential of Cilnidipine in Breast Cancer Cell Lines – An in Vitro Study (Journal of Pharmaceutical Negative Results, 2022)
Background: One of the malignancies that is most frequently diagnosed worldwide is breast cancer. According to recent data, approximately 2.3 million women worldwide receive a breast cancer diagnosis, and 6,85,000 of them pass away. One of the treatment modalities for breast cancer is chemotherapy. Chemotherapy can induce cytotoxicity in normal cells as well. Studies have shown cytotoxicity effects of calcium channel blockers. Cilnidipine is one of the dihydropyridine calcium channel blockers. The antioxidant effects of Cilnidipine have been observed through its benefits in cardioprotection, reno protection and neuroprotection. This study aims to find the anti-oxidant potential of Cilnidipine in MDA-MB 231 breast cancer cell lines.Methodology: The study was conducted in a tertiary care hospital , Chennai, Tamilnadu from December 2021-July 2022. The anti-oxidant activity is evaluated by Lipid peroxidase assay. In this assay, 4x105 MDA MB 231 cells were incubated for twenty-four hours. After incubation, the cells were either left untreated (control group) or given cilnidipine treatments at various concentrations. After this, the cells were exposed to 1 mM hydrogen peroxide for six hours to promote oxidative damage. Cells were taken after treatment and sonicated for 10 seconds to lyse them. The cell lysates were then centrifuged for 10 minutes at 4°C using 10,000 rotations per minute. The supernatants were then combined with a solution containing an equivalent volume of 0.375 TBA (thiobarbituric acid), 15% trichloroacetic acid, and 0.25 N HCl solution and were heated for 15 minutes in a boiling water bath before being centrifuged at 10,000 rotations per minute for 5 minutes. Finally, the supernatant's absorbance at 535 nm was determined.Result: Cilnidipine shows oxidative effect and produces cytotoxicity in the cancer cells.Conclusion: Cilnidipine causes cytotoxicity like conventional anti-cancer drugs by causing oxidative damage to the cancer cells.